Adult-plant resistance and a suitable method of reaction determination to scald and net form net blotch in malt barley genotypes at a hot spot location in Ethiopia - Girma Ababa; Tigist Shiferaw; Wami Hailu; Wondimu Fekadu; Sentayehu Alamerew (Discover Agriculture)
Abstract Scald and net form net blotch caused by fungal pathogens Rhynchosporium secalis and Pyrenophora teres f. teres, respectively, are significant foliar diseases affecting barley production on a global scale, and they lead to substantial reductions in both yield and quality. In the current study, the reactions of 100 malt barley genotypes to the diseases were evaluated under natural conditions in Ethiopia. Again, several methods of genotype reaction determination were assessed to select a suitable method. Field trial was conducted using a simple lattice design. The grain yield of ten middle rows (5 m2) was evaluated, and the results were converted to t ha−1. The relationship between independent and dependent variables was analyzed using the Pearson correlation in ellipses predictor at a P-value of 0.05 and 0.01. Logistic and Gompertz models were used for disease rate analysis. Genotypes HB#P786 and HB#P875 scored the highest (4.7 t ha−1) and lowest (0.8 t ha−1) grain yield, respectively. Eyal classes and Eyal and Brown reaction types were selected from several methods of genotype reaction determination. Out of one hundred genotypes evaluated, 41% were susceptible, 52% were moderately susceptible, 5% were moderately resistant, and 2% were resistant to scald disease. Genotypes such as HB#P1063 and HB#P239 were resistant to scald disease. Moreover, 16% were susceptible, 68% moderately susceptible, 12% were moderately resistant, and 4% were resistant to net form net blotch disease. Genotypes such as HB#P1063, HB#P239, SARC#41, and HB#P793 were resistant to net form net blotch disease. Therefore, these genotypes can be used for crop improvement in subsequent breeding schemes. A negative correlation (r = − 0.1) between plant height and leaf blotch severity indicated that the highest plant height genotype could be used for scald resistance. The current research suggests that the breeder can use the identified resistant and moderately resistant genotypes for future breeding schemes.